Notch signaling pathway modulation by food functional ingredients: mechanisms, cancer and immunoregulation - Nie, Rong-Zu; Luo, Huo-Min; Liu, Ya-Ping; Wang, Shuang-Shuang; Hou, Yan-Jie; Chen, Chen; Wang, Hang; Lv, Hui-Lin; Tao, Xing-Yue; Jing, Zhao-Hui; Zhang, Hao-Kun; Li, Pei-Feng (Frontiers in Cell and Developmental Biology, 2026)
This article comprehensively reviews the complex role of the Notch signaling cascade in cancer, as well as the regulatory mechanisms and potential anti-cancer effects of food functional ingredients on this pathway. The Notch signaling cascade is essential for maintaining normal cellular physiological processes and is closely associated with cancer initiation and progression; its abnormalities are linked to diverse biological behaviors of tumor cells, and it exhibits dual roles in both pro-cancer and anti-cancer properties. Food functional ingredients, including polyphenols, terpenoids, sulfur-containing compounds, vitamins, minerals, and other compounds, can precisely regulate the Notch signaling pathway via distinct molecular mechanisms and exert significant anti-cancer activity. In vitro cell experiments have elucidated the regulatory effects of these ingredients on the Notch pathway and their impacts on cancer cell phenotypes at the molecular level, while in vivo animal experiments further verified their efficacy in inhibiting tumor growth and metastasis. Although clinical research remains in its infancy, existing studies have provided directions for subsequent basic and clinical investigations-specifically, to further clarify the detailed mechanisms by which functional ingredients in food regulate the Notch signaling cascade and facilitate their clinical application in cancer treatment.